A New Strategy for Patient-Specific Implant-Borne Dental Rehabilitation in Patients With Extended Maxillary Defects - Korn, Philippe; Gellrich, Nils-Claudius; Jehn, Philipp; Spalthoff, Simon; Rahlf, Björn (Frontiers in Oncology, 2021)
Purpose of the study: Patients undergoing ablative tumor surgery of the midface are faced with functional and esthetic issues. Various reconstructive strategies, such as implant-borne obturator prostheses or microvascular tissue transfer, are currently available for dental rehabilitation. The present study shows the first follow-up of patients treated with patient-specific implants (IPS Implants® Preprosthetic) for the rehabilitation of extended maxillary defects following ablative surgery. Patients and Methods: All patients treated with patient specific implants due to postablative maxillary defects were included. 20 implants were placed in the 19 patients (bilateral implants were placed in one of the cases). In 65.75% of the cases, resection was performed due to squamous cell carcinoma. In addition to the primary stability, the clinical implant stability, soft tissue management, successful prosthodontic restoration, and complications were evaluated at a mean follow-up period of 26 months. Results: All patient-specific implants showed primary stability and were clinically stable throughout the observation period. Definitive prosthodontic restorations were performed in all patients. No implant loosening was observed. Major complications occurred only in previously irradiated patients with insufficient soft tissue conditions (p = 0.058). Minor complications such as exposure of the underlying framework or mucositis were observed, but they never led to failure of restorations or implant loss. Conclusions: Treatment of postablative maxillary defects with patient-specific implants offers a safe alternative with predictable results for full and rapid dental rehabilitation, avoiding time-consuming augmentation procedures and additional donor-site morbidity.